THE ROLE OF INSURANCE IN THE TRANSFORMATION PROCESS -SOME GENERAL REMARKS AND AN EXAMPLE - Eisen, Roland (Journal of European Economy, 2018)
The rapid transformation of former socialist countries to market economies and the necessary regulatory reforms will enable the insurance markets in Central and East Europe (CEE) to develop and expand significantly over the next few years. To discuss the development of the insurance sector, one first has to look at the macro-economic level, or in other words, at the financial stability of the economy. Therefore, sound macroeconomic and structural policies are essential for financial system stability to prevent or at least limit the emergence of serious financial imbalance, misleading price signals and distortions in incentives.